Plant Hormones Under Challenging Environmental Factors 2016
DOI: 10.1007/978-94-017-7758-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Phytohormones in Plant Responses to Ozone

Abstract: Among various contaminants, ozone (O 3 ) is considered the most ubiquitous and phytotoxic atmospheric pollutant in industrialized and developing countries. It causes extensive risks for plant life, in terms of survival and productivity of wild and cultivated species. Plant response to O 3 resembles the biotic defense reactions and includes two steps: the first is a biphasic oxidative burst with a massive, rapid, and transient increase in apoplastic reactive oxygen species (ROS) production; the second is the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 150 publications
2
26
0
Order By: Relevance
“…Hormone-dependent signals can act both independently and interactively to modulate the plant response to climate change (elevated CO 2 or O 3 ) and insect infestation ( Baier et al, 2005 ; Tamaoki, 2008 ; Erb et al, 2012 ; Zavala et al, 2013 ; Pellegrini et al, 2016 ). The hormone-mediated changes in host plant phenotypes under climate change can further affect the performance of herbivorous insects ( Guo et al, 2014 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormone-dependent signals can act both independently and interactively to modulate the plant response to climate change (elevated CO 2 or O 3 ) and insect infestation ( Baier et al, 2005 ; Tamaoki, 2008 ; Erb et al, 2012 ; Zavala et al, 2013 ; Pellegrini et al, 2016 ). The hormone-mediated changes in host plant phenotypes under climate change can further affect the performance of herbivorous insects ( Guo et al, 2014 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greenhouse gases, such as elevated CO 2 or O 3 , can modulate phytohormone-dependent signals in plants (Tamaoki, 2008;Pellegrini et al, 2016), and such priming defenses have significant consequences for the performance of herbivorous insects (Robinson et al, 2012;Zavala et al, 2013). In this study, we reported that elevated O 3 induced callose deposition in tomato plants and therefore enhanced plant resistance to B. tabaci in terms of reducing feeding efficiency and population abundance.…”
Section: Discussionmentioning
confidence: 76%
“…Signaling and cell death in O 3 -exposed plants have been reviewed by several authors (e.g., Rao et al, 2000; Rao and Davis, 2001; Kangasjärvi et al, 2005; Tamaoki, 2008; Vainonen and Kangasjärvi, 2015; Carmody et al, 2016; Pellegrini et al, 2016). Different plants use many hydraulic and chemical signals to tune their sensing of water deficit (Wilkinson and Davies, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is a physiological process that selectively targets and eliminates unwanted cells in response to a variety of biotic and abiotic stimuli ( Apel and Hirt, 2004 ). PCD resembles the hypersensitive response (HR) observed in several plant-pathogen interactions, which often precedes the acquisition of a systemic resistance by plants ( Kangasjärvi et al, 1994 ; Rao et al, 2000 ; Pellegrini et al, 2013 ; Vainonen and Kangasjärvi, 2015 ; Pellegrini et al, 2016 ). O 3 entering the leaves first induces a biphasic oxidative burst with a massive, rapid and transient increase in apoplastic reactive oxygen species (ROS), which is the main event leading to PCD activation ( Langebartels et al, 2002 ) Similarly, an oxidative burst was usually observed in plants under drought ( Smirnoff, 1993 ; Miller et al, 2010 ; Noctor et al, 2014 ) and the drought-triggered ROS production can elicit acclimatory events ( Smirnoff, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation